1997
DOI: 10.1023/a:1026313511646
|View full text |Cite
|
Sign up to set email alerts
|

Double Coupling Edman Chemistry for High-Sensitivity Automated Protein Sequencing

Abstract: Capillary electrophoresis with laser-induced fluorescence detection (CE-LIF) is a promising new method for the analysis of protein sequencing products. It gives 10 zmol (1 zmol = 10(-21) mol) limits of detection (3 sigma) for fluorescein thiohydantoin (FTH) amino acids. We have developed a separation for the (FTH)-amino acid products generated from 18 of the 20 coded amino acids. The extremely low volume requirement associated with CE-LIF makes it incompatible with commercial sequencers. For this reason, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The ionic group and fluorescent properties of the analyte also provides new alternatives such as CE separation and spectroscopic detection, for example, with sensitive fluorescence detection. Ireland et al showed, for example, that they could measure FTH-amino acids with a limit of detection on a low zeptomol (10 −21 ) level per injection by using CE separation with laser induced fluorescence detection [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic group and fluorescent properties of the analyte also provides new alternatives such as CE separation and spectroscopic detection, for example, with sensitive fluorescence detection. Ireland et al showed, for example, that they could measure FTH-amino acids with a limit of detection on a low zeptomol (10 −21 ) level per injection by using CE separation with laser induced fluorescence detection [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Ireland et al [21] showed that amino acids in proteins could be sequenced with FITC as Edman reagent and measured by CE-LIF with outstanding sensitivity. In order to test the same principle for adduct measurements without having access to a CE-LIF system we used CE-DAD to study the separation between FTH-Val and FTH-MeVal and measured the fluorescence properties separately.…”
Section: Discussionmentioning
confidence: 99%